A tamoxifen-inducible Cre knock-in mouse for lens-specific gene manipulation. (January 2023) - Wei, Zongbo; Hao, Caili; Chen, Jian-Kang; Gan, Lin; Fan, Xingjun
Abstract: Mouse models are valuable tools in studying lens biology and biochemistry, and the Cre-loxP system is the most used technology for gene targeting in the lens. However, numerous genes are indispensable in lens development. The conventional knockout method either prevents lens formation or causes simultaneous cataract formation, hindering the studies of their roles in lens structure, growth, metabolism, and cataractogenesis during lens aging. An inducible Cre-loxP mouse line is an excellent way to achieve such a purpose. We established a l ens-specific C re E RT2 k nock-in mouse (LCEK), an inducible mouse model for lens-specific gene targeting in a spatiotemporal manner. LCEK mice were created by in-frame infusion of a P2A-CreER T2 at the C-terminus of the last coding exon of the gene alpha A crystallin (Cryaa). LCEK mice express tamoxifen-inducible Cre recombinase uniquely in the lens. Through ROSA mT/mG and two endogenous genes (Gclc and Rbpj) targeting, we found no Cre recombinase leakage in the lens epithelium, but 50–80% leakage was observed in the lens cortex and nucleus. Administration of tamoxifen almost completely abolished target gene expression in both lens epithelium and cortex but only mildly enhanced gene deletion in the lens nucleus. Notably, no overt leakage of Cre activity was detected in developing LCEK lens when bred with mice carrying loxP floxed genes that are essential for lens development. This newly generated LCEK line will be a powerful tool to target genes in the lens for gene functions study in lens aging, posterior capsule opacification (PCO), and other areas requiring precision gene targeting. Highlights: A lens-specific knock-in Cre line is created. It is an inducible Cre KI mouse line allowing spatiotemporal gene targeting in the lens. Cre line is highly effective in gene deletion upon tamoxifen induction. Without tamoxifen induction, the Cre line does not affect lens development.